Impact of lockdown during COVID‐19 pandemic on physical activity and arrhythmia burden in heart failure patients. Issue 4 (17th January 2022) - Schmitt, Jörn; Wenzel, Beate; Brüsehaber, Bernd; Anguera, Ignasi; de Sousa, Joao; Nölker, Georg; Bulava, Alan; Marques, Pedro; Hatala, Robert; Golovchiner, Gregory; Meyhöfer, Jürgen; Ilan, Michael; et al.
Abstract: Background: Restricted outdoor activity during COVID‐19 related lockdown may accelerate heart failure (HF) progression and thereby increase cardiac arrhythmias. We analyzed the impact of March/April 2020 lockdown on physical activity and arrhythmia burden in HF patients treated with cardiac resynchronization therapy (CRT) devices with daily, automatic remote monitoring (RM) function. Methods: The study cohort included 405 HF patients enrolled in Observation of Clinical Routine Care for Heart Failure Patients Implanted with BIOTRONIK CRT Devices (BIO|STREAM.HF) registry in 16 countries, who had left ventricular ejection fraction (LVEF) ≤40% (mean 28.2 ± 6.6%) and NYHA class II/III/IV (47.9%/49.6%/2.5%) before CRT pacemaker/defibrillator implantation. The analyzed RM data comprised physical activity detected by accelerometer, mean heart rate and nocturnal rate, PP variability, percentage of biventricular pacing, atrial high rate episode (AHRE) burden, ventricular extrasystoles and tachyarrhythmias, defibrillator shocks, and number of implant interrogations (i.e., follow‐ups). Intraindividual differences in RM parameters before (4‐week period) versus during (4‐week period) lockdown were tested for statistical significance and independent predictors were identified. Results: There was a significant relative change in activity (mean −6.5%, p  < .001), AHRE burden (+17%, p  = .013), and follow‐up rate (−75%, p  < .001) during lockdown, with no significant changes in other RM parameters. Activity decreased by ≥8 min/day in 46.5% of patients; predictors were higher LVEF, lower NYHA class, no defibrillator indication, and more activity before lockdown. AHRE burden increased by ≥17 min/day in 4.7% of patients; predictors were history of atrial fibrillation, higher LVEF, higher body mass index, and activity decrease during lockdown. Conclusion: Unfavorable changes in physical activity, AHRE burden, and follow‐up rate were observed during lockdown, but not in ventricular arrhythmia.